De Novo Variant in GBX1 Gene Associated With Developmental Delay and Focal Epilepsy - Bingbing Zhang; Xiaohua Li; Xiao Qian; Jihong Tang (Molecular Genetics & Genomic Medicine, 2025)
ABSTRACT Background The gastrulation brain homeobox (Gbx) family, including GBX1 and GBX2, is crucial for hindbrain development and contributes to the morphogenesis of the midbrain–hindbrain boundary (MHB). While the role of the GBX1 gene in the development of the human nervous system remains to be elucidated, its variant in humans has not previously been reported to be associated with disease. Methods The patient presenting with sleep panic attacks underwent comprehensive clinical assessments, including electroencephalograph (EEG), magnetic resonance imaging (MRI), and genetic testing through whole exome sequencing (WES). Zebrafish models were generated through gbx1 gene crispants to investigate the functional impact of identified genetic variants. Results The patient in our study was diagnosed with focal epilepsy through long‐range EEG. WES revealed a de novo GBX1 gene variant [NM_001098834.3: c.910C>T (p.Gln304*)]. In zebrafish larvae with gbx1 gene disruption, significant abnormalities were observed in the morphology of the interocular area. Furthermore, these larvae exhibited an increased susceptibility to neurophysiological abnormalities associated with epileptiform activity. Conclusion Our study is the first to identify an association between the GBX1 gene variant and focal epilepsy. The zebrafish models confirmed the presence of related phenotypes in the gbx1‐Cas9. These findings underscore the significance of the GBX1 gene in neurological function.